One-pot multistep Henry-Michael reaction with notable upshots using reduced graphene oxide supported bifunctional catalysts - Dikin Patel; Sanjeev R. Kane; Chetan K. Modi (Catalysis Communications, 2022)
We concocted peculiar and exceedingly sound bifunctional MNPs/AA-rGO (MNPs = Fe and/or Nb2O5 nanoparticles; AA = aromatic and/or aliphatic primary amine derivatives such as benzene-1,4-diamine (BD) or ethylenediamine (ED); rGO = reduced graphene oxide) catalysts with an acid-base twofold activation mechanism bestowing base characteristics by the amine scaffold and Lewis acidic sites triggered by MNPs doped on the peripheral of rGO. Surprisingly, Nb2O5/BD-rGO demonstrated excellent performance for one-pot Henry-Michael reaction via acid-base supportive effect with 90.6 and 88.9% conversions of benzaldehyde and β-nitrostyrene, respectively, and an admirable product selectivity (i.e., 93.2%) of 2-(2-nitro-phenylethyl)malononitrile.